Migratory orientation in inexperienced and experienced avian migrants. Issue 3 (4th May 2021) - Åkesson, Susanne; Bakam, Himma; Martinez Hernandez, Elena; Ilieva, Mihaela; Bianco, Giuseppe
Abstract : Massive bird migration across continents and seas is one of the most spectacular phenomena in nature, involving billions of birds annually. In the autumn, most birds on migration are juveniles migrating for the first time while adults are repeating their migrations. Migration syndrome in individual bird migrants involves multiple behavioural, morphological and physiological adaptations, and migration performance may improve with experience and age. In this review, we discuss in what ways young and adult birds differ with respect to migration performance and compass orientation during migration, how they respond to external information including topography and winds during migration, and what phenotypic characteristics related to migratory behaviour may change over a lifetime in individual birds. Here, we present the prevailing concepts of navigation, including compass mechanisms leading birds across the globe to predictable goals, and the underlying sources of variability within and between individuals and age groups. In particular, we focus on what changes in the endogenous migration program may lead to more efficient realizations of migration with age. We review our data combined with other data presented in the literature, based on different techniques to study the migration phenotype expression in caged and free-flying birds with different migratory adaptations. The widespread use of tracking technology to study birds in different environments and geographical areas has largely contributed to our current knowledge on how migration performance improves with age. Still, there is a need to understand in more detail how migration performance, timing and route choices develop across time in individual migrants, and what navigational information is used to guide birds across the globe from the first and following migrations.